Evolutionary competition in microbial communities: from population dynamics to single-cell behavior - Oliveira, N (2015)
Microbial life in nature is typically associated with two distinctive features: (i) the formation of densely packed groups, mostly on surfaces, within which social interactions are rife, and (ii) mixing with multiple strains and species, which brings with it the potential for strong evolutionary conflict. However, most microbiology still rests upon the study of single genetic backgrounds, often in shaking flasks. There is a need then to better integrate the natural ecology and evolution of microbes into microbiological studies. My thesis combines ecoevolutionary theory with the empirical study of both population dynamics and single-cell behavior to understand social interactions within microbial communities. This systems biology approach suggests that competition, not cooperation, is central to understanding diverse microbial communities and can explain key social phenotypes including cross-feeding, biofilm formation and antibiotic resistance. Specifically, I study the theoretical limits for cooperation within microbial communities and conclude that natural selection will rarely favor cooperation between genotypes; I show that antibiotic competition between strains is an important driver of biofilm formation, which is consistent with the idea of competition sensing (the ability to use antibiotics, or more generally any form of biotic stress, as a cue to detect and respond to ecological competition); I establish the behavioral and genetic basis of chemotaxis on surfaces at the single-cell level and discuss how this phenotype can be useful in the social milieu of microbial communities where positioning is a major determinant for evolutionary competition; and finally, I show that bacteria are able to climb antibiotic gradients via twitching chemotaxis and achieve an unprecedented level of resistance in a few hours by simply modulating their physiology. Again, and as for antibiotic-induced biofilm formation, I argue that this perplexing phenotype has its natural roots in competition sensing. The study of microbial interactions has emphasized the importance of cooperation between cells of a single genotype. My thesis shows the need to consider the other side of microbial interactions: evolutionary competition. A cell will commonly face intense competition from other strains and species, and only by appreciating this evolutionary conflict will we fully understand microbes and their complex communities.